Pengaruh Model Pembelajaran Student Team Achievement Division (STAD) terhadap Hasil Belajar Teknik Dasar Passing dan Dribbling dalam Permainan Handball pada Siswa Kelas XI.9 dan XI.10 di SMA Negeri 1 Nengara (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model on the learning outcomes of basic passing and dribbling techniques in handball among students of class XI.9 and XI.10 at SMA Negeri 1 Negara. The research was conducted using a quantitative approach with an experimental design involving two groups, namely the experimental group which received the STAD learning model treatment, and the control group which used conventional learning. Data were collected through pretest and posttest assessments that encompassed the affective, cognitive, and psychomotor aspects of the students. The results of the assumption test indicated that the data from both groups were normally distributed and homogeneous, allowing for data analysis to proceed using parametric statistical techniques. The results of the paired sample t-test indicate that both the experimental and control groups experienced a significant improvement in learning outcomes from the pretest to the posttest across all measured aspects. However, based on the results of the independent sample t-test, no significant difference in improvement was found between the experimental group and the control group. This means that both the STAD learning model and the conventional model are equally effective in improving learning outcomes, but there is not a statistically strong difference between the two.